Associations between perimenopausal status, depression, sexuality, and FSH levels in Women: A cross-sectional study. - Asad, Kanza; Fatima, Mushkbar; Nisar , Muhammad (International Journal of Endorsing Health Science Research, 2024)
Background: Perimenopause, the phase preceding menopause, is characterized by hormonal, cultural, and socio-familial changes. It is associated with increased follicular phase and serum follicle-stimulating hormone (FSH) levels, potentially impacting lifestyle and contributing to sexual dysfunction during the menopausal transition. This study aimed to establish associations between lifestyle factors, depression, attitudes towards sexuality, FSH levels, and perimenopausal status among females. Methodology: A cross-sectional study was conducted among women aged 30-50 years in Karachi hospitals. Data were collected from a total of 80 females, categorized into two groups: the premenopausal period (age 30 to 40) as the control group and the perimenopausal period (age 40 to 50) as the study group. Blood samples were analyzed to measure serum FSH levels, while questionnaires were administered to assess depression, sexuality attributes, and FSH levels. Results: The study revealed that perimenopausal women exhibited higher levels of depression and secretory phase serum FSH compared to the control group, along with lower attitudes towards sexuality. Notably, attitudes towards sexuality were significantly diminished in the perimenopausal group compared to the control group (p < 0.005). Conclusion: In conclusion, the endocrine events associated with perimenopause contribute to depression, declining sexual function during the menopausal transition, and age-related increases in FSH levels among regularly cycling women.